Managerial Revolution in Islamic Education in Indonesia: Enhancing Quality Through Innovative Approaches - Syukron, Buyung; Josiah, Trisnowati; Hasan, Maryan (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
In the transformation and development of Islamic education, various challenges are faced, particularly in improving the quality of management and the relevance of learning. This study examines the managerial revolution in Islamic education through innovative approaches aimed at enhancing the quality of management and teaching within Islamic educational institutions. The method employed is a literature review, which gathers and analyzes various relevant literatures on innovations in the management of Islamic education, including journals, books, articles, and research reports. The approaches applied in this study include transformational leadership and strategic management, which are believed to create significant changes in the management of Islamic education, enabling it to address contemporary challenges. The primary focus of this research is to analyze the application of various innovative approaches, such as the use of technology in learning, the enhancement of leadership skills in educational management, and the development of a curriculum that is both relevant and adaptable to the evolving needs of society. The aim of this research is to explore how innovative managerial revolutions can improve the quality of Islamic education through the implementation of new approaches and provide practical recommendations for educators, education managers, and policymakers in creating a more dynamic and high-quality educational environment. The results indicate that the implementation of innovative approaches in the management of Islamic education can lead to positive impacts on the overall quality of education. The integration of technology, transformational leadership, and a relevant curriculum are key elements in creating a more effective and efficient education system. Despite the significant challenges, innovations in the management of Islamic education can bring about meaningful changes to improve the quality and relevance of Islamic education in Indonesia.